EFEKTIVITAS UU NO 18 TAHUN 1998 TERHADAP JASA-JASA PERBANKAN - PURBA, JULIANA; Ukas, Ukas (LPPM Universitas Putera Batam, 2024)
According to Law no. 10 of 1998, banks are business entities that collect funds from the public in the form of savings (funding), distribute them to the public in the form of credit (lending) and provide other services in order to improve the standard of living of many people. The regulation of banking governance in Indonesia is in accordance with the spirit of the meaning of MPRS Decree Number MPRS/1966 basically aims to be able to mobilize and develop potential economic power to be deployed to increase people''s prosperity.This type of research is normative legal research, namely legal research carried out by examining library materials or secondary data, also called doctrinal research, where law is often conceptualized as what is written in statutory regulations (law in books) or conceptualized as rules or Norms are standards for human behavior that are considered appropriate. Bank services are banking activities carried out by a bank to facilitate the activities of collecting funds and distributing funds. The more complete the bank services provided, the better it will be, thereby attracting customers. This is because customers feel comfortable carrying out financial activities from just one bank.